Streptococcal infection and autoimmune diseases - Ohashi, Ayaka; Murayama, Masanori A.; Miyabe, Yoshishige; Yudoh, Kazuo; Miyabe, Chie (Frontiers in Immunology, 2024)
Excessive activation of immune cells by environmental factors, such as infection or individual genetic risk, causes various autoimmune diseases. Streptococcus species are gram-positive bacteria that colonize the nasopharynx, respiratory tract, gastrointestinal tract, genitourinary tract, and skin. Group A Streptococcus (GAS) species cause various symptoms, ranging from mild infections, such as tonsillitis and pharyngitis, to serious infections, such as necrotizing fasciitis and streptococcal toxic shock syndrome. The contribution of GAS infections to several autoimmune diseases, including acute rheumatic fever, vasculitis, and neuropsychiatric disorders, has been studied. In this review, we focus on the association between streptococcal infections and autoimmune diseases, and discuss current research on the mechanisms underlying the initiation and progression of autoimmune diseases.